2019
DOI: 10.3899/jrheum.180582
|View full text |Cite
|
Sign up to set email alerts
|

Scleroderma Renal Crisis: Risk Factors for an Increasingly Rare Organ Complication

Abstract: Objective.Scleroderma renal crisis (SRC) is a severe life-threatening manifestation in patients with systemic sclerosis (SSc). However, the knowledge about risk factors for SRC is limited. We determined here the frequency of SRC and identified risk factors for the prediction of SRC.Methods.Based on regular followup data from the German Network for Systemic Scleroderma, we used univariate and multivariate generalized estimating equations to analyze the association between clinical variables, SSc subsets, therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 37 publications
2
14
0
9
Order By: Relevance
“…Other explanations could account for our SMR within the lower range of published data such as a lower number of diffuse cutaneous subtype of SSc (16.8% vs. 23.4% to 46%) [8][9][10][11]19,[43][44][45][46][47] , a lower number of patients with a SRC (2.4% compared to 2.9%-10%) [9][10][11]19,43,47], and a less extended level of cutaneous involvement (average Rodnan skin score of 6.8 for the patients in the present study vs. 9) [11]. Regarding SRC, we described the same incidence as in the recent German epidemiological study evaluating renal involvement on 2873 patients with SSc [48]. In addition, we kept in our analysis SSc sine scleroderma, which is often excluded from such studies that could explain our relatively low SMR.…”
Section: Discussionsupporting
confidence: 74%
“…Other explanations could account for our SMR within the lower range of published data such as a lower number of diffuse cutaneous subtype of SSc (16.8% vs. 23.4% to 46%) [8][9][10][11]19,[43][44][45][46][47] , a lower number of patients with a SRC (2.4% compared to 2.9%-10%) [9][10][11]19,43,47], and a less extended level of cutaneous involvement (average Rodnan skin score of 6.8 for the patients in the present study vs. 9) [11]. Regarding SRC, we described the same incidence as in the recent German epidemiological study evaluating renal involvement on 2873 patients with SSc [48]. In addition, we kept in our analysis SSc sine scleroderma, which is often excluded from such studies that could explain our relatively low SMR.…”
Section: Discussionsupporting
confidence: 74%
“…The independent risk factor with the highest probability of SRC for autoantibodies is positive anti-RNA polymerase III antibodies. [5] In our case, ANA was positive in 1/1000 granular pattern; anti-topoisomerase I, anti-centromere, and anti RNA polymerase III were negative, and also regarding antiphospholipid antibodies, anti-cardiolipin IgG and IgM, anti-beta 2 glycoprotein IgA, IgM, and IgG were negative as well as lupus anticoagulant. When evaluated clinically, features related to kidney function were not helpful in predicting the renal crisis.…”
Section: Discussionsupporting
confidence: 47%
“…DcSSc was diagnosed in 57.1% of these patients, lcSSc in 31.4%, and overlap syndromes in 11.4%. [5] Pre-vious studies noted that patients with dcSSc had a higher risk of up to 25% with SRC. [6] SRC was observed in only 1% of patients with lcSSc.…”
Section: Discussionmentioning
confidence: 99%
“…Rapidly progressive skin thickening appears to be the main risk factor for SRC, with most dcSSc patients developing SRC within 7.5 months to 4 years of disease onset [10, 11, 42]. According to Moinzadeh et al [43], development of proteinuria and/or hypertension, as well as positive anti-RNA polymerase III (anti-RNAP III) antibodies are the strongest risk factors for SRC. Terras et al [44] and Stochmal et al [45] showed that the presence of anti-RNAP III antibodies in patients with SSc correlates with renal crisis and severe cutaneous involvement.…”
Section: Scleroderma Renal Crisismentioning
confidence: 99%